The Effect of Chemical Activation Using Base Solution With Various Concentrations Towards Sarulla Natural Zeolite - Saharman Gea; Agus Haryono; Andriayani Andriayani; Junifa Layla Sihombing; Ahmad Nasir Pulungan; Tiamina Nasution; Rahayu Rahayu; Yasir Arafat Hutapea (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : Material characteristics analysis of Sarulla natural zeolite (SNZ) with base activation has been carried out. The base used was NaOH at various concentrations; 0.2 M, 0.5 M, and 2 M. Base activated catalysts were characterized by X-ray Fluorescence (XRF), X-ray diffractometer (XRD), Fourier-transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscopy (SEM) and gas adsorption analysis using BET method. The procedures applied have caused differences in adsorption and desorption rates as well as the crystallinity values of the catalytic materials. Moreover, the ratio of Si/Al contents has also changed at the lowest concentration. On the other hand, the crystallinity of catalysts has decreased at the highest concentration of base applied. The results are reinforced in FTIR characterization which shows the changes of silanol bonds to become silicate and aluminate. Furthermore, morphological analysis of the catalysts shows that homogenous surface was obtained at low concentration, while rough/lumpy surfaces was obtained at higher concentration.Abstrak : Analisis terhadap karakteristik material dari zeolit alam Sarulla (SNZ) dengan metode aktivasi basa telah dilakukan. Basa yang digunakan ialah NaOH dengan berbagai konsentrasi; 0,2 M; 0,5 M, dan 2 M. Katalis yang telah diaktivasi dengan basa kemudian dikarakterisasi dengan Analisis X-ray Fluorescence (XRF), X-ray diffractometer (XRD), Fourier-transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscopy (SEM) dan Gas Adsorption menggunakan metode BET. Dari hasil penelitian, ditemukan perbedaan pada tingkat adsorpsi dan desorpsi, begitu juga dengan kristalinitas pada material katalis. Lebih jauh, rasio konten Si/Al juga berubah pada basa dengan konsentrasi terendah. Di sisi lain, tingkat kristalinitas dari katalis mengalami penurunan pada basa dengan konsentrasi tertinggi. Hasil ini diperkuat dengan data FTIR yang menunjukkan perubahan ikatan silanol menjadi silikat dan aluminat. Lebih jauh, analisis morfologi pada katalis menunjukkan bahwa permukaan yang homogen didapatkan dari penggunaan basa dengan konsentrasi rendah. Sebaliknya, basa dengan konsentrasi tinggi memberikan bentuk permukaan katalis yang tidak homogen serta kasar.